IPTEKS PERAN PENGAWASAN BPKP DALAM MENGAWAL DAN MENGOPTIMALKAN PENERIMAAN NEGARA - Adi, R. Haryo Wiratama; Elim, Inggriani (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Non-tax state revenues are sources of Indonesian state revenues originating from levies paid by individuals or entities, where all proceeds of such revenues are managed by the government in which the proceeds from the direct or indirect benefits of services and utilization of resources and rights obtained from the state, based on taxation legislation. The purpose of this study is to ensure that government bureaucracy (governance) punishes achieving goals by implementing risk management and control. BPKP as an APIP that has authority based on the law and presidential regulation in the management of PNBP, must be proactive, initiative, anticipative to help formulate, plan, implement policies for monitoring PNBP management.Keywords: government internal control apparatus, goverment, regulation in the managemeent of PNBP